Um estudo grafemático das letras G e J em português - Gama, Viviane Lima de Oliveira (2007)
This study is situated on the area of Portuguese Language Description and deals with the examination of the letters g and j , by means of verifying the existence of rules regarding the use of these letters in the orthographic system, contributing to the graphemic studies of the Portuguese Orthography. The carried out research is based on the proposal of Derrida (1967), on the studies of Nina Catash (1973) and on the research meetings carried out in France in 1973 and 1986. Thus, it is understood that the methods used by Phonology can be extended to Graphemics, as well as its theoretical models. It is justified once it is understood that the oral system presents distinct traces, different from the orthographic system in Brazil, where few studies under the prism of Graphemics had been carried out so far. It is stated as hypothesis that some rules can be described for the use of the letters g and j preceding the vowels e and i , where difficulties for the orthographic use occur. The acquired results indicate that: a) the letter g differs from the letters j as the former belongs to the Portuguese Language etymologic system and the latter to the phonetic system. Therefore, the letter g spells the poliphonologic values /g, / and the letter j , the poliphonologic value / /; b) there are commutative pairs between g and j , by means of considering them two graphemes of the Portuguese Language orthographic system: the grapheme g of the etymologic system, in complementary distribution with a , o , u and the grapheme g in complementary distribution with e , i . In this sense, the distinctive trace of the grapheme g + /a, o, u/ belongs to the Portuguese Language orthographic subsystem and g + /e, i/ to the phonetic etymologic system. The grapheme j spells the phoneme / / of the language phonetic system for new words, entries for the Portuguese Language; but j spells words of i, y etyma of origins other than Latin, for being palatal in the Portuguese Language entry; for this reason, they are the etymologic-phonetic trace; c) there is no graphemic change on word derivation, unless due to the complementary distribution, by means of spelling g for the etymologic-phonetic trace and j for the phonetic trace; d) in the Portuguese Language history, the latin etyma present a single letter to spell /g, /, depending on the vowel that follows; the grapheme j spells the palatization previous to any vowel, being it oral or nasal; e) Other considerations. Due to the existent confusion relating to the etyma of the Portuguese Language words, it was verified that there are two ways of spelling the same word, both with g and j . It is concluded, from these occurrences, that it is possible to deal with the Portuguese Language orthographic system through theoretical and methodological models of Phonology. However, due to the unawareness of etyma, specific studies in the area are necessary to guide future Orthographic Changes